The Integration of Responsibility Accounting and Corporate Governance and its Impact on Improving Banking Performance - Miaad Hameed Ali; Lect Nadia Shakir Hussein (Academic Bright Collaboration, 2026)
Purpose – This study examines the level of implementation of responsibility accounting and corporate governance mechanisms, and analyzes the impact of their integration on improving banking performance. Methods – The study adopts a quantitative approach using primary data collected through structured questionnaires. The sample consists of managers and employees from 12 banks, including departments of profit, cost, revenue, and investment, as well as senior and middle management. A total of 65 questionnaires were distributed, with 54 valid responses analyzed using descriptive statistics to assess implementation levels and the perceived impact of integration. Findings – The results indicate that both responsibility accounting and corporate governance are implemented at a relatively high level. More importantly, their integration demonstrates a positive and significant influence on banking performance. This is evidenced by a high mean score of 4.46 and a standard deviation of 0.62, reflecting strong consensus among respondents. The integration supports clearer delegation of authority, improved accountability, and more effective performance evaluation, which collectively contribute to better organizational outcomes. Research implications – The study is limited by a small sample size and reliance on perceptual data, which may affect generalizability. However, it provides practical insights for improving internal control and decision-making through the integration of responsibility accounting and corporate governance. Originality – This study fills a research gap by examining the integration of responsibility accounting and corporate governance, showing that their alignment enhances performance evaluation, accountability, and organizational control.